2023
DOI: 10.1093/heapro/daad082
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Australian MATES in Construction Suicide Prevention Program: a systematic review

Jorgen Gullestrup,
Tania King,
Samantha L Thomas
et al.

Abstract: Suicide is a major public health issue globally. The World Health Organization has called for nations to create comprehensive national suicide prevention strategies including multisectoral collaboration, awareness raising, advocacy and capacity building. The workplace provides opportunity and structure for suicide prevention programs. However, many of these programs are poorly documented and evaluated. The MATES in Construction (MATES) program is a multimodal workplace-based suicide prevention program designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Peer support has been evidenced to be critical to psychosocial safety in the construction work environment, and this sample demonstrated minimal concern with this item compared to previous COVID-19 data [ 25 , 36 ]. This sample in the NT was garnered from sites that had a strong peer support network and a training program attached to suicide prevention and mental health awareness, including accreditation with MATES in Construction [ 25 ]. Further exploration of work environments where these factors are not present could demonstrate how significant peer support is to worker wellbeing and give broader clarity to peer support in the Northern Territory building and construction industry.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Peer support has been evidenced to be critical to psychosocial safety in the construction work environment, and this sample demonstrated minimal concern with this item compared to previous COVID-19 data [ 25 , 36 ]. This sample in the NT was garnered from sites that had a strong peer support network and a training program attached to suicide prevention and mental health awareness, including accreditation with MATES in Construction [ 25 ]. Further exploration of work environments where these factors are not present could demonstrate how significant peer support is to worker wellbeing and give broader clarity to peer support in the Northern Territory building and construction industry.…”
Section: Discussionmentioning
confidence: 56%
“…Similarly, role ambiguity and poor relationships are strong features of stress in the construction work environment [ 24 ]. Peer support and the perception of an understanding and trustworthy work environment is an additional known protective factor for workplace mental health [ 25 ]. This point is further evidenced in the experiences of workers themselves; having trusted and reliable peers and established relationships is known to strengthen construction workers’ sense of support and community when facing mental health adversity or distress [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies reported a significant increase in confidence around help-offering, this did not translate to any increased willingness to offer help or incidences of help-offering behavior. This may be explained by the lack of clear ''help-offering'' construct definitions despite its use in the wider literature (Gullestrup et al, 2023), outcome measures with poor psychometric properties, and the short-term nature of the interventions. While significant changes were observed post-intervention in the included studies, the extent to which these findings can be attributed to intervention effects is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond this, a number of industry-speci c risk factors have been reported such as low job control, high work demands, job insecurity, the transient nature of work and long work hours (12)(13)(14). Other studies that have reported factors associated with CIW suicide include young age, low education, nancial, legal and relationship issues, low socioeconomic status, alcohol misuse, migration, and depression (14)(15)(16).This emerging body of evidence has prompted the development and implementation of early intervention programmes within the construction industry which have shown promise in reducing sigma, improving suicide prevention literacy and improving intention to seek help and offer help to colleagues (17,18). However, researchers are often limited in their ability to evaluate the direct and indirect effects of such early intervention programmes on suicide due to the relatively low base-rate behaviour and the subsequent requirement to have prohibitively large sample sizes (19), and because most variables of interest cannot be measured postmortem (8).…”
Section: Introductionmentioning
confidence: 99%